Cointegration and Consumption Risks in Asset Returns - Bansal, Ravi; Dittmar, Robert; Kiku, Dana (Review of Financial Studies, 2009)
We argue that the cointegrating relation between dividends and consumption, a measure of long-run consumption risks, is a key determinant of risk premia at all investment horizons. As the investment horizon increases, transitory risks disappear, and the asset's beta is dominated by long-run consumption risks. We show that the return betas, derived from the cointegration-based VAR (EC-VAR) model, successfully account for the cross-sectional variation in equity returns at both short and long horizons; however, this is not the case when the cointegrating restriction is ignored. Our evidence highlights the importance of cointegration-based long-run consumption risks for financial markets.